2018
DOI: 10.1186/s40594-018-0118-3
|View full text |Cite
|
Sign up to set email alerts
|

A study of the correlation between STEM career knowledge, mathematics self-efficacy, career interests, and career activities on the likelihood of pursuing a STEM career among middle school students

Abstract: Background: A sample of 1448 students in grades 7 and 9 was drawn from public schools in Atlantic Canada to explore students' knowledge of science and mathematics requirements for science, technology, engineering, and mathematics (STEM) careers. Also explored were their mathematics self-efficacy (MSE), their future career interests, their preferences for particular career activities, and their likelihood to pursue a STEM career.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
155
1
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 192 publications
(167 citation statements)
references
References 37 publications
8
155
1
3
Order By: Relevance
“…Out of the six published in 2017, three are on mathematics education (Hagman et al 2017;Keller et al 2017;Ulrich and Wilkins 2017) and the other three on either teacher professional development (Borko et al 2017;Jacobs et al 2017) or connection with engineering (Jehopio and Wesonga 2017). For the five published in 2018, two are on mathematics education (Beumann and Wegner 2018;Wilkins and Norton 2018) and the other three have close association with other disciplines in STEM (Blotnicky et al 2018;Hayward and Laursen 2018;Nye et al 2018). This trend likely reflects a growing interest, with close connection to mathematics, in both mathematics education community and a broader STEM education community of developing and sharing multidisciplinary and interdisciplinary scholarship.…”
Section: Notesmentioning
confidence: 99%
“…Out of the six published in 2017, three are on mathematics education (Hagman et al 2017;Keller et al 2017;Ulrich and Wilkins 2017) and the other three on either teacher professional development (Borko et al 2017;Jacobs et al 2017) or connection with engineering (Jehopio and Wesonga 2017). For the five published in 2018, two are on mathematics education (Beumann and Wegner 2018;Wilkins and Norton 2018) and the other three have close association with other disciplines in STEM (Blotnicky et al 2018;Hayward and Laursen 2018;Nye et al 2018). This trend likely reflects a growing interest, with close connection to mathematics, in both mathematics education community and a broader STEM education community of developing and sharing multidisciplinary and interdisciplinary scholarship.…”
Section: Notesmentioning
confidence: 99%
“…In the USA, Wang and Degol (2016) found six explanations for women's underrepresentation in STEM fields: (a) cognitive ability, (b) relative cognitive strengths, (c) occupational interests or preferences, (d) lifestyle values or work/family balance preferences, (e) field-specific ability beliefs, and (f) gender-related stereotypes and biases. As the size and composition of the STEM workforce continuously fails to meet the demand (Jang 2016;Wang & Degol, 2016), it is important to understand the barriers and factors that influence individual education and career choices (Blotnicky, Franz-Odendaal, French & Joy, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Students with higher mathematics self-efficacy and STEM career knowledge are more likely to choose a STEM career (Blotnicky et al 2018;. In addition, students' own beliefs that success in science depends on exceptional talent can negatively impact their motivation to learn as well as a lack of enjoyment and confidence (Lin-Siegler, Ahn, Chen, Fang, & Luna-Lucero, 2016;Wu, Deshler, & Fuller, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In this next phase of the project, the inclusion of STEM career and educational opportunities as well as enhanced computer science experiences have been added because research indicates that these are educational areas that need bolstering, especially in the middle school students. Exposure to STEM careers can elevate student interest in pursuing careers involving science, technology, engineering and mathematics (Blotnicky, Franz-Odendaal, French, & Phillip, 2018). Emphasis must be placed on the inclusiveness of underrepresented populations in the STEM fields.…”
Section: Figure 2 the Billion Oyster Project -Curriculum And Communimentioning
confidence: 99%
“…The importance of creating a thriving STEM workforce in the United States has been promoted for the last decade. Studies have shown that capturing students' interest must occur before they enter high school, ideally in the middle school years (Blotnicky, Franz-Odendaal, French, & Phillip, 2018). Teachers are the conduits for encouraging students to explore STEM-related career options.…”
mentioning
confidence: 99%